Amide-linked monocarbonyl curcumin analogues: efficient synthesis, antitubercular activity and molecular docking study - Subhedar, Dnyaneshwar D.; Shaikh, Mubarak H.; Nagargoje, Amol A.; Akolkar, V. Satish; Bhansali, Sujit G.; Sarkar, Dhiman; Shingate, Bapurao B. (Polycyclic Aromatic Compounds, 2022)
An approach toward the synthesis of novel conjugates of 3,5-bis (arylidene)-4-piperidones (DAP) pharmacophore with amide-linkage has been developed via one-pot multicomponent reaction of aryl aldehydes, piperidinone and 2-chloro-N-phenylacetamide using [Et3NH][HSO4] as a catalyst/medium. Both substitutions on arylidene rings and piperidinone nitrogen (substituted 2-chloro-N-phenylacetamide) were varied. The synthesized conjugates were evaluated for their in vitro antitubercular activity against M. tuberculosis H37Ra (MTB) and M. bovis BCG strains. Among the series, compounds 4f, 4g, 4i and 4j showed remarkable broad spectrum antitubercular activity with low IC50 values. Furthermore, computer docking simulations, for the most active conjugates were performed with the active site of mycobacterial enoyl-acyl carrier protein reductase (InhA) support the antitubercular activity. Lower cytotoxicity, high potency and promising activity against MTB and M. Bovis BCG suggest that amide linked DAP could serve as good leads for further modifications and development.
Keywords: antimycobacterial activity; Bis (arylidene)-4-piperidones; Cytotoxicity; Ionic liquid; Molecular docking Study

[DBUH][OAc]-catalyzed domino synthesis of novel benzimidazole incorporated 3,5-Bis (Arylidene)-4-piperidones as potential antitubercular agents - Subhedar, Dnyaneshwar D.; Shaikh, Mubarak H.; Nagargoje, Amol A.; Sarkar, Dhiman; Khedkar, Vijay M.; Shingate, Bapurao B. (Polycyclic Aromatic Compounds, 2022)
A series of new benzimidazole incorporated 3,5-bis (arylidene)-4-piperidones were synthesized by using aryl aldehydes, piperidinone, 2-(chloromethyl)-benzimidazole and DBU acetate [DBUH][OAc] act as a catalyst under solvent free condition in excellent yields. The synthesized compounds were screened for their in vitro antimycobacterial activity against M. tuberculosis H37Ra (MTB) and M. bovis BCG strains. The compounds 4a, 4b, 4e, 4i, 4k and 4l are highly potent against both the strains. Most of the active compounds are non-cytotoxic against MCF-7, A549, HCT 116 and THP-1 cell lines. Furthermore, a molecular docking study of these compounds was carried out to investigate their binding pattern with the target, active site of mycobacterial enoyl-acyl carrier protein reductase (Inh A). Therefore, these compounds can be subjected for further optimization and drug development which could give promising chemical leads for treatment of TB.
Keywords: Antitubercular activity; curcumin; Cytotoxicity; Ionic liquid; multicomponent reactions

Tetrazoloquinoline-1,2,3-triazole derivatives as antimicrobial agents: synthesis, biological evaluation and molecular docking study - Shaikh, Mubarak H.; Subhedar, Dnyaneshwar D.; Akolkar, Satish V.; Nagargoje, Amol A.; Khedkar, Vijay M.; Sarkar, Dhiman; Shingate, Bapurao B. (Polycyclic Aromatic Compounds, 2022)
In search of new active molecules, a small focused library of tetrazoloquinoline-based 1,2,3-triazoles has been efficiently preparedviaclick chemistry approach. Several derivatives were found to be exhibiting promising antimicrobial and antioxidant activity characterized by their lower minimum inhibitory concentration values. All the synthesized compounds exhibited excellent antibacterial activity against Gram negative bacteriaE. coliandF. devoransand antifungal activity againstC. albicansandA. niger. Further, these compounds were tested for their antitubercular activity against dormantMTB H37Raand dormantM. bovis BCGusing XRMA assay protocol and showed no significant activity. Also, the synthesized compounds were found to have potential antioxidant activity with IC(50)range = 12.48-50.20 mu g/mL. Furthermore, to rationalize the observed biological activity data, the molecular docking study also been carried out against the active site of fungalC. albicansenzyme P450 cytochrome lanosterol 14 alpha-demethylase, which revealed a significant correlation between the binding score and biological activity for these compounds. The results of thein vitroandin silicostudy suggest that the triazole-incorporated tetrazoloquinolines may possess the ideal structural requirements for further development of novel therapeutic agents.
Keywords: 1; 2; 3-Triazole; ADME prediction; Antimicrobial; Antioxidant; Docking study

[DBUH][HSO4]-catalyzed solvent-free synthesis of 1,5-benzodiazepine derivatives: bioevaluation and in silico molecular docking study - Subhedar, Dnyaneshwar D.; Shaikh, Mubarak H.; Nagargoje, Amol A.; Sarkar, Dhiman; Khedkar, Vijay M.; Shingate, Bapurao B. (Current Organic Chemistry, 2025)
Here, we report the solvent-free one-pot multicomponent synthesis of 4-substituted-1,5-benzodiazepine derivatives from O-phenylenediamine, aromatic aldehydes, and dimedone using [DBUH][HSO4] as a catalyst in excellent yields. This process was carried out in search of a reusable, easily accessible, affordable, and efficient catalyst. 1,5-Benzodiazepines demonstrate a new family of good inhibitors with potent anti-mycobacterial properties. The most promising compounds in the present series are 4c, 4i, and 4l which showed excellent activity and inhibited the growth of both MTB H37Ra and M. bovis BCG strains with lower MICs. The most active compounds were further studied for their cytotoxicity against cell lines MCF-7, A549, HCT116, and THP-1 by MTT assays and the compounds were found to be non-toxic. The fact that none of these compounds work against either Gram-positive or Gram-negative bacteria suggests that they are only effective against MTB. The in silico docking of the molecules against mycobacterial enoyl reductase, InhA enzyme could provide well-clustered solutions and have given valuable insights into the thermodynamic elements governing the binding affinities. The findings of this investigation unmistakably point to the discovery of extremely specific and selective MTB inhibitors, which can now be investigated further in search of possible anti-tubercular drugs.
Keywords: 1; 5-benzodiazepine; Antitubercular activity; Molecular docking; multicomponent reactions; [DBUH][HSO4]